Employee Training as A Mediator in The Influence of Coaching Leadership and Employee Relationships on Employee Well-being - Yuanita, Irene Arliana; Pramudianto (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
The purpose of this study is to analyze the effect of coaching leadership and employee relationships on employee well-being through employee training as a mediating variable. The subject of this study was employees of PDAM Tirta Sembada. This study used purposive sampling. The number of respondents in this study was 152 employees. The method used to analyze research results is Partial Least Square with SmartPLS software version 4.1.0.0. The result shows that coaching leadership and employee relationships have a direct and positive effect on employee training and also employee well-being. Employee training has a direct and positive effect on employee well-being. Employee training can complementary mediate the relationship between coaching leadership and employee well-being and also the relationship between employee relationship and employee well-being.